Characterization of Anti-seizure Medication Treatment Pathways in Pediatric Epilepsy Using the Electronic Health Record-Based Common Data Model - Kim, Hunmin; Yoo, Sooyoung; Jeon, Yonghoon; Yi, Soyoung; Kim, Seok; Choi, Sun Ah; Hwang, Hee; Kim, Ki Joong (Frontiers in Neurology, 2020)
The purpose of this pilot study was to analyze treatment pathways of pediatric epilepsy using the common data model (CDM) based on electronic health record (EHR) data. We also aimed to reveal whether CDM analysis was feasible and applicable to epilepsy research. We analyzed the treatment pathways of pediatric epilepsy patients from our institute who underwent antiepileptic drug (AED) treatment for at least 2 years, using the Observational Medical Outcomes Partnership (OMOP)-CDM. Subgroup analysis was performed for generalized or focal epilepsy, varying age of epilepsy onset, and specific epilepsy syndromes. Changes in annual prescription patterns were also analyzed to reveal the different trends. We also calculated the proportion of drug-resistant epilepsy by applying the definition of seizure persistence after application of two AEDs for a sufficient period of time (more than 6 months). We identified 1192 patients who underwent treatment for more than 2 years (mean ± standard deviation: 6.5 ± 3.2 years). In our pediatric epilepsy cohort, we identified 313 different treatment pathways. Medication refractoriness, calculated as the application of more than three AEDs during the first 2 years of treatment, was 23.8%. Treatment pathways and medication refractoriness differed between subgroups of generalized vs. focal epilepsy, different onset age of epilepsy, and specific epilepsy syndromes. The frequency of AED prescription was similar between onset groups of different ages; however, phenobarbital was frequently used in children with epilepsy onset less than 4 years. Ninety-one of 344 cases of generalized epilepsy and 187 of 835 cases of focal epilepsy were classified as medically intractable epilepsy. The percentage of medical refractoriness was markedly different depending on the specific electro-clinical epilepsy syndrome (79.0% for Lennox-Gastaut syndrome [LGS], 7.1% for childhood absence epilepsy [CAE], and 9.0% for benign epilepsy with centrotemporal spikes [BECTS]). We could visualize the annual trend and changes of AED prescription for pediatric epilepsy in our institute from 2004 to 2017. We revealed that CDM analysis was feasible and applicable for epilepsy research. The strengths and limitations of CDM analysis should be carefully considered when planning the analysis, result extraction, and interpretation of results.